Development of Module Based on Scientific Contextual Additives Material to Increase Learning Outcomes and Science Process Skills in Junior High School - Martiningsih, Ika; Lisdiana, Lisdiana; Susilowati, Sri Mulyani Endang (Journal of Innovative Science Education, 2019)
This study aims to increase learning outcomes and science process skills of students using modules based on scientific contextual. This is a type of research and development (R&D) with the development procedure of Sugiyono's model with the pre-experimental design method with the form of one group pretest posttest design. Increased student learning outcomes and science process skills is explored through the observation sheet, then analyzed using N-gain. The results showed that modules based on scientific contextual could increase student learning outcomes with N-gains of 0.481 (medium) in class VIII 6 and 0.446 (medium) in class VIII 7. Science process skills of students experienced an increase in each aspect namely observing, classification, interpreting, and communication with N-gain acquisition amounting to 0.08 (low); 0.05 (low); 0.25 (low); and 0.07 (low) for class VIII 6, while science process skills in class VIII 7 experienced an increase in each aspect with N-gain acquisition equal to 0.3 (medium); 0.3 (medium); 0.5 (medium); and 0.5 (medium). Based on the results of the analysis, it can be concluded that the development of modules based on scientific contextual effectively increasing student learning outcomes and science process skills.